2019
DOI: 10.17583/ijelm.2019.3758
|View full text |Cite
|
Sign up to set email alerts
|

Leading and Teaching with Technology: School Principals’ Perspective

Abstract: Technology has changed the way people live, from use of the Internet to the way they communicate with text messages and e-mails. This change is also evident in the education system. This study traced how principals' leadership roles have changed in the school setting because digital natives and society, in general, have become technologically savvy. The findings for this study were generated from interviews and observations of high school principals. This qualitative research study revealed that administrators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 15 publications
0
21
0
16
Order By: Relevance
“…That is, the framework utilized in this study draws attention to not only whether leaders have time for reflection but also whether they are open to identifying their immunities to change and altering their own personal beliefs that might get in the way of change. Ugur and Koc (2019), in a study of leaders' views of technology, indicated that administrators interviewed had strong beliefs that technology should be implemented. Juxtaposed with the current framework, questions may be raised about the possibility of such principals being transparent about their belief systems (e.g., technology, data analysis within teams) with others in the school, and additionally being open to how one's belief system might prevent one from seeing others' perspectives and validating those other perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…That is, the framework utilized in this study draws attention to not only whether leaders have time for reflection but also whether they are open to identifying their immunities to change and altering their own personal beliefs that might get in the way of change. Ugur and Koc (2019), in a study of leaders' views of technology, indicated that administrators interviewed had strong beliefs that technology should be implemented. Juxtaposed with the current framework, questions may be raised about the possibility of such principals being transparent about their belief systems (e.g., technology, data analysis within teams) with others in the school, and additionally being open to how one's belief system might prevent one from seeing others' perspectives and validating those other perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…They must develop their ability to develop a vision for the use of technology in the institution in the future. They must develop their ability to integrate technology in the learning environment and realize the significance of such integration (Uğur & Koç, 2019) 8. Empirical Studies: Hayat et al (2015) explored the training needs of high school principals in Shiraz, Iran.…”
Section: Definitionsmentioning
confidence: 99%
“…There is no denying the role of information technology in improving the quality of school instructions (Afshari et al, 2009). Especially, the latest advancements of artificial intelligence, automation, and educational technology, etc., have brought an extremely diverse and rich knowledge flatform, and useful tools for school leaders, making access to professional knowledge and academic community much simpler and simultaneously maximizing the effectiveness of school leadership (Tam et al, 2017;Uğur & Koç, 2019). Inevitably, education during the COVID-19 pandemic has changed dramatically with the distinctive rise of e-learning thanks to the advancement of information technology.…”
Section: Advancement Of Information Technologymentioning
confidence: 99%
“…educational management software, cloud computing, STEM materials or robotics, etc., can come to schools depends on the innovative thinking and courage of school leaders (Sincar, 2013). The advancement of science and technology entails high investment and training costs, and schools may be faced with solving problems regarding the effectiveness and quality of training programs (Sincar, 2013;Uğur & Koç, 2019). The explosion of educational technology will then create non-traditional modes of educational leadership and gradually change perspectives and approaches to school management and leadership.…”
Section: Advancement Of Information Technologymentioning
confidence: 99%
See 1 more Smart Citation